2005
DOI: 10.1038/sj.bjc.6602315
|View full text |Cite
|
Sign up to set email alerts
|

Lack of EGF receptor contributes to drug sensitivity of human germline cells

Abstract: Germline mutations have been associated with generation of various types of tumour. In this study, we investigated genetic alteration of germline tumours that affect the drug sensitivity of cells. Although all germline tumour cells we tested were hypersensitive to DNA-damaging drugs, no significant alteration was observed in their DNA repair activity or the expression of DNA repair proteins. In contrast, germline tumours expressed very low level of epidermal growth factor receptor (EGFR) compared to drug-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Increased cell growth and survival upon overexpression or activity of the EGF receptor is associated with resistance to anticancer treatments such as hormone therapy, chemotherapy and radiotherapy in various tumor types [8190]. Many experimental studies demonstrate that inhibition of the EGF receptor in cancer cells enhances the effect of conventional chemotherapeutics by increasing apoptosis in vitro or causing arrest of tumor growth in vivo , but the results in clinical trials are mixed [reviewed in 8891].…”
Section: Consequences Of Egf Receptor Activation In Ovarian Cancermentioning
confidence: 99%
“…Increased cell growth and survival upon overexpression or activity of the EGF receptor is associated with resistance to anticancer treatments such as hormone therapy, chemotherapy and radiotherapy in various tumor types [8190]. Many experimental studies demonstrate that inhibition of the EGF receptor in cancer cells enhances the effect of conventional chemotherapeutics by increasing apoptosis in vitro or causing arrest of tumor growth in vivo , but the results in clinical trials are mixed [reviewed in 8891].…”
Section: Consequences Of Egf Receptor Activation In Ovarian Cancermentioning
confidence: 99%
“…However, studies have shown that EGFR overexpression in ovarian cancer cells indicates an increase in drug resistance. Suppressing EGFR expression in ovarian cancer cells increases cisplatin sensitivity (23)(24)(25). Following OCT binding with SSTR, the activation of the tyrosine phosphatase and the reversal of EGF-induced EGFR tyrosine kinase phosphorylation results in the reduction of EGFR, the termination of EGF signal transduction at the cell membrane and, eventually, the inhibition of cell proliferation (23).…”
Section: Discussionmentioning
confidence: 99%
“…Each group consisted of three parallel wells, and each experiment was repeated three times for each group. For the OCT group, cells were cultured for predetermined times (24,48,72 and 96 h). Then, the cells were treated with 20 µl of the 3-(4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide (MTT) reagent (500 µg/ml) for 4 h, and lysed in 150 µl of dimethyl sulfoxide solvent reagent for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Germline mutations, one of genetic alterations, exist in all cells in body and can be inherited (4,5). Germline mutations are associated with generation of various tumors and drug resistance (6)(7)(8). A recent American study found that 16.1% of RCC patients carried germline mutations in a RCC predisposition gene, and some cases of early-onset aggressive RCC without defined pathogenic germline mutations have been observed (9).…”
Section: Introductionmentioning
confidence: 99%